Effectiveness of geropsychiatric home treatment concerning parameters of physical health: matched-pair study - Christa Peinhaupt; Gernot Fassolder; Wolfgang Habacher; Monika Singer; Gerhard Hermann; Günter Klug (BJPsych Open, 2021)
Background There is evidence of the effectiveness of multi-professional home treatment models with regards to improving mental health for elderly patients with mental illness. However, there is a lack of studies examining the efficacy with regard to physical health.